Absence motivated by illness: A non-concurrent prospective study of physical education teachers in the municipal education system of the city of Campinas, São Paulo, Brazil - Franco, Ana Cláudia Santurbano Felipe; Gonçalves, Aguinaldo; Padovani, Carlos Roberto (My University, 2009)
The object of this investigation was to identify and analize aspects of the health status related to absenteism in physical education teachers in the municipal education system of the city of Campinas, Brazil, as related to the medical leave program. The non-concurrent prospective study was accomplished by means of a comparison with teachers who work only in the classroom, refering to a three year period. In the variables of greatest interest, the Pearson non-parametric chi-square (X2) statistical test was adopted. Calculations of relative risk and level of confidence were made using the Epi-info computer program. Significant differences were observed in the following diagnostic groups favoring the not exposed group: i) Supplementary Classification of factors that exercise influence over the health status and access to health services and ii) Digestive system illness; while the physical education teachers showed a significant difference in: i) diseases of the musculoskeletal and connective tissue system and ii) Injuries and poisoing. Possible explications for some of the adverse effects as well as the protective ones that were observed include physical activity as a way of life along with being a physical education teacher and on the other side, peculiar behavior of epidemiological descriptive characteristics, like sex and age, within the socio-economic context of the country. © Copyright Moreira Jr. Editora.
Keywords: Physical education; Public health; Teaching; Work absence; absenteeism; adult; Brazil; city; computer program; connective tissue disease; digestive system disease; female; health care access; health status; human; injury; intoxication; major clinical study; male; motivation; musculoskeletal disease; physical education; prospective study; risk assessment; teacher